Synthesis and Evalution of Some Novel Semicarbazone Derivatives for Anticonvulsant Activity - Banjare, Laxmi (International Journal of Pharmaceutical & Biological Archive, 2012)
Synthesis and Evalution of Some Novel Semicarbazone Derivatives for Anticonvulsant Activity